PEMANFAATAN MASJID AL-IKHLAS SEBAGAI SENTRA BIMBINGAN BELAJAR DI KELURAHAN GELUGUR MEDAN TIMUR - Batubara, Ismail Hanif; Julianti, Lisa (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The COVID-19 pandemic has had a serious impact on all life on earth. The world of education, including other sectors, must adapt quickly. Likewise in terms of education must adapt in tackling this pandemic. One of the efforts made in tackling this pandemic is by holding tutoring for students, especially elementary school students who have only received learning through gadgets or whatsapp media by their teachers without getting an explanation beforehand so they don't understand what they are studying. This community service was carried out at the Al-Ikhlas Mosque in the neighborhood of Gelugur Darat, Medan Timur. The method used in the form of providing tutoring for one month. The results obtained in the provision of tutoring is a positive response from the National Mosque Council and parents of students. Parents are very supportive and greatly helped by the existence of tutoring which is carried out free of charge. Another result is that students learn to be independent in doing school assignments, and some of them are able to read and count.